2022
DOI: 10.12681/mms.29218
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean spreading of the bicolor purse oyster, Isognomon bicolor, and the chicken trigger, Malleus sp., vs. the Lessepsian prejudice

Abstract: The introduction rate of alien species in the Mediterranean Sea is rapidly growing, and their taxonomical identification is increasingly challenging. This uncertain identification often leads to an incorrect estimation of the number of alien species, their route of introduction, and their potential negative effects. This is particularly true for some bivalves, which are characterized by high variation in their shells, resulting in uncertain morphological identification. This is the case for two alien bivalves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Moreover, larvae of tropical species could be recruited locally under more favourable thermal conditions, such as those in the Levantine basin, and subsequently disperse westwards. Thus, the I. bicolor population recorded in both study areas may have acted as a donor pool for the southeastern coast of Italy, in accordance with Garzia et al (2022). In this study, although eastwards dispersal is easily assumed for I. bicolor, it is likely that Ionian colonization is a result of secondary dispersal from the Aegean Sea.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, larvae of tropical species could be recruited locally under more favourable thermal conditions, such as those in the Levantine basin, and subsequently disperse westwards. Thus, the I. bicolor population recorded in both study areas may have acted as a donor pool for the southeastern coast of Italy, in accordance with Garzia et al (2022). In this study, although eastwards dispersal is easily assumed for I. bicolor, it is likely that Ionian colonization is a result of secondary dispersal from the Aegean Sea.…”
Section: Discussionsupporting
confidence: 79%
“…Their identi cation was corroborated by DNA barcoding. The rst record of I. bicolor in the Mediterranean Sea was recently documented and con rmed with molecular tools (Garzia et al 2022). Despite the numerous records of I. legumen in the Mediterranean Sea (see above), its identi cation using molecular methods was con rmed for the rst time in the Mediterranean Sea by this study.…”
Section: Discussionmentioning
confidence: 94%
“…Angelidis & Polyzoulis (2018) described the diagnostic characters to distinguish I. legumen from I. australica , and after that paper, more records of the latter species followed from the eastern Mediterranean ( Manousis et al, 2021 ; Albano et al, 2021a ). Because the identification of specimens was often disputed by later authors, Garzia et al (2022) performed a molecular analysis that showed that specimens morphologically similar to the earliest Mediterranean records in Libya ( Crocetta, 2018 ) and Israel ( Mienis et al, 2016 ) and identified as the Indo-Pacific I. legumen belong in fact to the Caribbean species Isognomon bicolor (C. B. Adams, 1845). However, the morphological characters highlighted by Angelidis & Polyzoulis (2018) to distinguish the alleged I. legumen from I. australica looked robust in our opinion and deserved further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…This last point becomes even more necessary if species with an extremely variable and confounding phenotype are involved, like in the case of some Haminoeidae species. In fact, several taxonomic errors in mollusks have been revealed and resolved in recent decades thanks to integrative systematic studies [7,8,[49][50][51] which, have highlighted the complexity of natural environments and of the interactions between species and the very complicated evolutionary patterns that can be generated.…”
Section: Discussionmentioning
confidence: 99%